Variation in Seed Yield, Oil Quality, and Seed Elements of Sunflower as Affected by Various Fertilizers and Tillage Systems. Issue 3 (4th February 2023) - Aryafar, Siavash; Sirousmehr, Alireza; Khammari, Issa; Ghanbari, Ahmad; Seyedabadi, Esmaeel
ABSTRACT: This study was performed to investigate the effect of various fertilizers and tillage systems on seed yield, oil quality, and seed elements of sunflower (Shams cultivar). The experiment was conducted in a split-plot design with three replications at research field of University of Zabol (Chahnimeh) in 2019 and 2020. The main factor included three tillage methods (A1 : moldboard plow + disc, A2 : chisel plow + disc and A3 : disc). Subfactor includes six fertilizer combinations :(B1 : no fertilizer application, B2 : 100 kg/ha of diammonium phosphate, B3 : 25 tons/ha of livestock manure +100 kg/ha of diammonium phosphate, B4 : 50 tons/ha of livestock manure +100 kg/ha of diammonium phosphate, B5 : 25 tons/ha of livestock manure, B6 : 50 tons/ha of livestock manure). Results showed that in the first year, the highest seed yield (5072 Kg/ha) and percentage of oleic acid (51.61%) was achieved from A3 B6 . In the second year, the highest seed yield (8003 Kg/ha) with A1 B5 and the highest oleic acid (53.87%) was obtained from A2 B2 . Application of A2 B2 treatment composition produced the highest nitrogen content in the seed (0.625%) and application of A3 B6 produced the highest potassium content in the seed (11.652 mg/g). In general, by considering the reduction of tillage in the field and improving the traits of sunflower, the application of A3 B6 is recommended to improve the percentage of oleic acid, phosphorus, and potassium contents and 1000-seed weight and if the conventional tillage is used, B2 can be recommended to improve seed yield, calcium content, and oil content.